2020
DOI: 10.1038/s41419-020-2336-0
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circRNF20 promotes breast cancer tumorigenesis and Warburg effect through miR-487a/HIF-1α/HK2

Abstract: Compelling evidence has demonstrated the potential functions of circular RNAs (circRNAs) in breast cancer (BC) tumorigenesis. Nevertheless, the underlying mechanism by which circRNAs regulate BC progression is still unclear. The purpose of present research was to investigate the novel circRNA circRNF20 (hsa_circ_0087784) and its role in BC. CircRNA microarray sequencing revealed that circRNF20 was one of the upregulated transcripts in BC samples. Increased circRNF20 level predicted the poor clinical outcome in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
158
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(163 citation statements)
references
References 28 publications
(28 reference statements)
5
158
0
Order By: Relevance
“…In recent years, a wide variety of medical therapies have been proposed for Osteosarcoma, including surgery, chemotherapy, radiotherapy, hormonotherapy, and small molecular targeting treatments. Indeed, we have obtained promising results, as previously reported, the prognosis of OS patients without metastasis is generally excellent, and the five-year survival is greater than 60% [3]. Nevertheless, the prognosis of patients with advanced disease is very poor because of the recurrence and distant metastasis [4].…”
Section: Introductionsupporting
confidence: 61%
“…In recent years, a wide variety of medical therapies have been proposed for Osteosarcoma, including surgery, chemotherapy, radiotherapy, hormonotherapy, and small molecular targeting treatments. Indeed, we have obtained promising results, as previously reported, the prognosis of OS patients without metastasis is generally excellent, and the five-year survival is greater than 60% [3]. Nevertheless, the prognosis of patients with advanced disease is very poor because of the recurrence and distant metastasis [4].…”
Section: Introductionsupporting
confidence: 61%
“…18 Cao et al claimed that circ-RNF20 accelerated the progression and glycolysis of breast cancer cells through regulating miR-487a/ HIF-1α/HK2 axis. 19 The expression pattern and working mechanism of HK2 in PCa were investigated in this study.…”
Section: Introductionmentioning
confidence: 99%
“…36 It is characterized by high glucose uptake, active glycolysis and high lactate production in metabolites. 37 Reprogramming of energy metabolism consequently results in high accumulation of lactate in the tumour microenvironment. 38 Recent findings shown that lactate was positively correlated with higher incidence of metastases, tumour progression and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%